Achieving highly efficient electrocatalytic oxygen evolution with ultrathin 2D Fe-doped nickel thiophosphate nanosheets. (May 2018) - Liang, Qinghua; Zhong, Lixiang; Du, Chengfeng; Luo, Yubo; Zheng, Yun; Li, Shuzhou; Yan, Qingyu
Abstract: Exploring earth-abundant electrocatalysts to realize efficient oxygen evolution reaction (OER) is highly desired for developing sustainable electrochemical energy storage and conversion technologies. Herein, ultrathin single-crystalline Fe-doped nickel thiophosphate (NiPS3 ) nanosheets prepared in large scale by an easy solid-state method were demonstrated to be highly efficient OER electrocatalysts. The density functional theory (DFT) calculations reveal that the Fe-doping effectively decreases the energy barrier of OER path by reducing the binding of the oxygen-containing species on the surface of NiPS3 . As such, the Fe-doped NiPS3 nanosheets show a low overpotential of 256 mV to reach a current density of 30 mA cm −2 and a small Tafel slope of 46 mV dec −1 . To our knowledge, this is one of the best OER electrocatalysts in alkaline medium to date. The in-depth mechanism study demonstrates that the in-situ formed Fe-doped nickel oxides/hydroxides shell, resulting from the surface oxidation during the OER process, not only may serve as favorable electrocatalytic species but also improves the chemical stability of the Fe-doped NiPS3 in alkaline electrolyte. This work provides a new perspective for designing highly efficient OER electrocatalysts based on the ternary two-dimensional layered metal thiophosphates. Graphical abstract: Ultrathin 2D Fe-doped NiPS3 nanosheets exhibit highly efficient electrocatalytic water oxidation with a low overpotential of 256 mV reach a current density of 30 mA cm −2 and small Tafel slope of 46 mV dec −1 as well as good stability. fx1 Highlights: Ultrathin Fe-doped NiPS3 nanosheets were prepared by a scalable solid-state method. The Fe-doped NiPS3 nanosheets exhibit superior electrocatalytic water oxidation. Fe-doping effectively decreases the energy barrier of oxygen evolution. The formed Fe-doped nickel oxides/hydroxides shell improves thestability.